‘Is it wise to open up America again now?’ Learning from government responses to COVID-19 and economy reopen points in three Asia-Pacific countries - Yu, Jia; Pang, Yulei (British Journal of Healthcare Management, 2020)
With the continuously increasing number of new confirmed COVID-19 cases, many health experts worried about the possibility of a ‘second wave’ outbreak, which might cause more deaths and hit economies even worse. This article looks at the experiences of fighting COVID-19 from three Asia-Pacific countries and discusses whether it is a wise decision to open up America again at this time.
2 citations (Crossref) [2023-10-31] tex.ids: yuItWiseOpen2020a
Keywords: dept.eco; dept.mat; peer-reviewed

No more nursing homes? Changes in consumer preferences for long-term care facilities following COVID-19 - Schultz, Amber F; Yu, Jia (British Journal of Healthcare Management, 2020)
Since the first COVID-19 case was discovered in December 2019, over 12.1 million cases have been reported in more than 188 countries and territories. In the USA, the Centers for Disease Control and Prevention has confirmed almost 3.05 million COVID-19 cases, with more than 132 000 deaths. The COVID-19 pandemic has had a particularly dramatic impact on the elderly and those with chronic underlying medical disorders. Before the second outbreak in July, long-term care facilities were the most severely affected in terms of case numbers, especially nursing homes. This article provides information and insight into the potential changes in consumer preferences toward long-term care facility selection and the possible structural change of the long-term care industry in three aspects; structure, conduct and performance. © 2020 MA Healthcare Ltd. All rights reserved.
1 citations (Crossref) [2023-10-31]
Keywords: Covid-19; Home care service; Long-term care facility; Nursing home; dept.eco; peer-reviewed